2016
DOI: 10.1371/journal.pone.0150495
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Metabolite GWAS Hits: Implication of CPS1 and the Urea Cycle in Weight Maintenance

Abstract: Background and ScopeWeight loss success is dependent on the ability to refrain from regaining the lost weight in time. This feature was shown to be largely variable among individuals, and these differences, with their underlying molecular processes, are diverse and not completely elucidated. Altered plasma metabolites concentration could partly explain weight loss maintenance mechanisms. In the present work, a systems biology approach has been applied to investigate the potential mechanisms involved in weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Although our model provides a seemingly relevant physiological context for the GWAS finding reported here and by others (Demirkan et al, 2015;Hartiala et al, 2016;Matone et al, 2016;Xie et al, 2013) of the strong association of glycine levels with SNPs in and downstream of the 3 0 UTR of the CPS1 gene, it remains unclear how these SNPs actually regulate glycine levels. It also remains to be demonstrated that CPS1 expression or activity is altered by these SNPs.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although our model provides a seemingly relevant physiological context for the GWAS finding reported here and by others (Demirkan et al, 2015;Hartiala et al, 2016;Matone et al, 2016;Xie et al, 2013) of the strong association of glycine levels with SNPs in and downstream of the 3 0 UTR of the CPS1 gene, it remains unclear how these SNPs actually regulate glycine levels. It also remains to be demonstrated that CPS1 expression or activity is altered by these SNPs.…”
Section: Discussionmentioning
confidence: 87%
“…Five recent genome-wide association studies (GWASs) found that circulating glycine levels are strongly associated with variants in the gene encoding carbamoyl phosphate synthase 1 (CPS1) (Demirkan et al, 2015;Hartiala et al, 2016;Matone et al, 2016;Mittelstrass et al, 2011;Xie et al, 2013), the rate-limiting enzyme in the urea cycle. Importantly, the rs715 CPS1 variant, which is associated with lower levels of urea cycle intermediates and elevated glycine, is also significantly associated with protection from coronary artery disease (Hartiala et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We found that glycine mediated the relationship between CPS1 and BMI, WHR, IL‐6, and HOMA‐IR, such that lower CPS1 expression was associated with higher levels of glycine, which were associated with lower BMI, WHR, IL‐6, and HOMA‐IR. Relationships between CPS1 , glycine, and cardiovascular risk factors have been hypothesized recently, but not clearly defined (Matone et al, ; Xie et al, ). The CPS1 gene encodes for a mitochondrial enzyme that catalyzes the first step of the hepatic urea cycle by synthesizing carbamoyl phosphate from ammonia, bicarbonate, and two molecules of ATP, and is important for removal of urea from cells (Haberle et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…CPS1 variants have been linked to CPS1 deficiency (Haberle et al, ), neonatal pulmonary hypertension (Pearson et al, ), vascular function (Summar et al, ), traits related to blood clotting, such as fibrinogen levels and platelet count (Astle et al, ; Danik et al, ; de Vries et al, ; Sabater‐Lleal et al, ), homocysteine levels (Lange et al, ; Pare et al, ; van Meurs et al, ; Williams et al, ), HDL cholesterol (Willer et al, ), kidney function and disease (Gorski et al, ; Kottgen et al, ; Mahajan et al, ; Pattaro et al, ), AD (Jun et al, ), and BMI (Locke et al, ; Melen et al, ). Higher adipose tissue expression of CPS1 has been associated with detrimental traits, including weight gain (Matone et al, ). At least nine studies have reported associations between CPS1 variants and glycine (Demirkan et al, ; Draisma et al, ; Kettunen et al, ; Long et al, ; Raffler et al, ; Shin et al, ; Suhre et al, ; Xie et al, ; Yu et al, ) and others have reported associations with betaine, a derivative of glycine (Hartiala et al, ; Long et al, ; Shin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…BCAR1 (Kazakova et al, 2018) and CAMK2B (Sacco et al, 2016) also have higher ranks in muscle-WDIN which were 289 and 257 respectively. PPARG (Voight et al, 2010) was ranked 533 in adipose-WDIN, while CPS1 (Matone et al, 2016) had an unsatisfied rank 1,272. In general, the ranked results of these 8 genes were basically consistent with their published results associated with T2D.…”
Section: Resultsmentioning
confidence: 99%